Degrees of Epithelial Dysplasia in Tounge induced by Candida albicans in Immunosupressed Condition - Dwi Andriani; Agni Febrina Pargaputri; Syamsulina Revianti (Denta Journal Kedokteran Gigi, 2019)
Background: Candida albicans is a common opportunistic pathogen that play a significantrole in Oral candidiasis and mucosal carcinogenesis. Several studies founD that Candida sp.associated with dysplastic alteration in the epithelium. Candida present in oral cavity withepithelial change is one of predisposing factor of candida infection and lead to atypia to dysplasia. Immunosupression condition is predisposition factor of oral candidal infection.Objective: To investigate the degree of epithelial dysplasia in tounge induced by Candidaalbicans in immunosuppred condition. Methods: This study was true experimental withposttest-only control group design. Sixteen healthy male Rattus novergicus (Wistar), 12 weeksand 200-250 g weight, were immunosuppressed through oral administration ofdexamethasone and tetracycline for 21 days and induced with C.albicans (ATCC-10231) 1Mc.Farland. The subjects were divided into 4 groups (n=4/group): healthy (HG),immunosuppressed (IG), Immunosupressed+Candida albicans (ICG), and nystatintreatment(NG). The subjects were treated for 14 days, later the rats were euthanized and theirtongue being biopsied. Epithelial dysplasia was subjected to HE examination, observed undera microscope (400x magnification) and statistically analyzed (Kruskall wallis, Mann withey, p<0.05). Result: Epithelial dysplasia of IG was the heaviest than other group. No eptithelialchange were found in group HG. Significant differences existed between HG with othergroups; IG with ICG; ICG with NG (p<0.05). No significant differences was present betweenIG and NG (p > 0.05). Conclusion: There was epithelial change in the tongue both inimmunosupressed condition with or without induction Candida albicans. Degree of epithelialdysplasia in tounge induced by Candida albicans in immunosupressed condition group wasthe heaviest than other group.